Principles of Marketing / Third European Edition - Armstrong Gary; Kotler Philip; Saunders John; Wong Veronica (Financial Times - Prentice Hall, 2002)
One of the leading and most authoritative marketing textbook. Preface, Acknowledgements, Marketing and the Marketing Process, Marketing in a Changing World: Satisfying Human Needs, Marketing and Society: Social Responsibility and Marketing Ethics, Strategic Marketing Planning, The Marketing Setting, The Marketing Environment, The Global Marketplace, Consumer Buyer Behavior, Business-to-Business Marketing, Market Information and Marketing, Core Strategy, Market Segmentation and Targeting Satisfying Human Needs, Positioning, Building Customer Relationship: Customer Satisfaction and Quality and Value and Service, Product, Brands and Products and Packaging and Support Services, New-Product Development and Product Life-Cycle Strategies, Marketing Services, Price, Pricing Considerations and Approaches, Pricing Strategies, Promotion, Integrated Marketing Communication Strategy, Mass Communications: Advertising and Sales Promotion and Public Relations, Personal Selling and Sales Management, Place, Managing Marketing Channels, Subject index, Glossary.